Building and using a model of insurgent behavior to avoid IEDS in an online video game - Rogers-Ostema, Patrick J. (Kansas State University, 2010)
IEDs are a prevailing threat to today’s armed forces and civilians. With some IEDs being well concealed and planted sometimes days or weeks prior to detonation, it is extremely difficult to detect their presence. Remotely triggered IEDs do offer an indirect method of detection as an insurgent must monitor the IED’s kill zone and detonate the device once the intended target is in range. Within the safe confines of a video game we can model the behavior of an insurgent using remotely triggered IEDs. Specifically, we can build a model of the sequence of actions an insurgent goes through immediately prior to detonating an IED. Using this insurgent model, we can recognize the behavior an insurgent would exhibit before detonating an IED. Once the danger level reaches a certain threshold, we can then react by changing our original course to a new one that does not cross the area we believe an IED to be in. We can show proof of concept of this by having human players take on the role of an insurgent in an online video game in which they try to destroy an autonomous agent. Successful tactics used by the autonomous agent should then be good tactics in the real world as well.
Keywords: Learning; Fuzzy logic; Adaptive strategies; Human behavior analysis; Virtual world; Online game; Computer Science (0984)